Release of rosmarinic acid from semisolid formulations and its penetration through human skin ex vivo - Stelmakienė Ada; Ramanauskienė Kristina; Briedis Vitalis (Acta Pharmaceutica)
The aim of this study was to evaluate the release of rosmarinic acid (RA) from the experimental topical formulations with the Melissa officinalis L. extract and to evaluate its penetration through undamaged human skin ex vivo. The results of the in vitro release study showed that higher amounts of RA were released from the emulsion vehicle when lemon balm extract was added in its dry form. An inverse correlation was detected between the released amount of RA and the consistency index of the formulation. Different penetration of RA into the skin may be influenced by the characteristics of the vehicle as well as by the form of the extract. The results of penetration assessment showed that the intensity of RA penetration was influenced by its lipophilic properties: RA was accumulating in the epidermis, while the dermis served as a barrier, impeding its deeper penetration.